A Study on Student Perception of Virtual Dissection Table (Anatomage) at GSL Medical College, Rajahmundry - Bharati, Amit Singh; N, Surya Kumari; Rani, V. Subhashini (Academia Anatomica International, 2018)
Introduction: The Anatomage Table is the only fully segmented real human 3D anatomy system. Individual structures are reconstructed in accurate 3D and it helps the medical pre-clinical students to explore and understand human anatomy like never before and even beyond a cadaveric dissection. Anatomage is an interface that affords students the opportunity to explore life-size anatomy on an interactive 3D table.[1] Aim and Objective: The aim of the study was to gather student opinion regarding this virtual dissection table (Anatomage) technology. Subjects and Methods: A questionnaire addressing the role of the Anatomage table in anatomy education and its comparison with various other learning modality was completed by 150 pre-clinical medical students. A free hand comment section was also included in the study. Results: 96% of students strongly preferred the cross sectional planes and images of Anatomage over still images of text book in learning Anatomy. 95% of students strongly agreed that the ability of Anatomage to rotate and dissect is better in visualizing the body systems. 90% of students strongly agreed that Anatomage can be an adjunct or added tool to cadaveric dissection but not its replacement.48% of students believe Anatomage visualisation is better than real dissected structures. Conclusion: Anatomage can play an important role in the acquisition of 3D knowledge of Anatomy and promises to be a useful added tool to traditional learning modalities, which still ranked high. This feedback also reveals that students are fascinated with the inclusion of Anatomage in their curriculum as it helps them in understanding, revising and learning in a better way than before. This virtual dissection table can be of immense help in medical colleges where sufficient number of cadavers are not available for Anatomical study.